2016
DOI: 10.1161/hypertensionaha.115.06608
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of Unilateral Nephrectomy in Living Kidney Donors

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
107
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(118 citation statements)
references
References 49 publications
7
107
0
4
Order By: Relevance
“…We found 9 studies, 614 not including the current study 15, 16 reporting possible mineral and bone disorders in kidney donors (Table S1). Of the previous 9 studies, 5 were prospective, comparing changes before and after donation but did not include normal controls.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…We found 9 studies, 614 not including the current study 15, 16 reporting possible mineral and bone disorders in kidney donors (Table S1). Of the previous 9 studies, 5 were prospective, comparing changes before and after donation but did not include normal controls.…”
Section: Discussionmentioning
confidence: 98%
“…16 Despite reduced levels of serum phosphate, tubular resorption of phosphate declined (Table 3), indicating that renal phosphate excretion was the likely cause, or at least a contributing factor to the lower serum phosphate concentrations. Although 3 studies reported no change in serum phosphate concentrations, 6, 10, 14 3 others reported a decline in phosphate after kidney donation. 7, 11, 13 All studies that measured tubular resorption of phosphate reported a decline after donation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations